2013
DOI: 10.1242/jcs.125757
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive neural stem cells become invasive in vitro by combinatorial FGF2 and BMP4 signaling

Abstract: SummaryNeural stem cells (NSCs) typically show efficient self-renewal and selective differentiation. Their invasion potential, however, is not well studied. In this study, Sox2-positive NSCs from the E14.5 rat cortex were found to be non-invasive and showed only limited migration in vitro. By contrast, FGF2-expanded NSCs showed a strong migratory and invasive phenotype in response to the combination of FGF2 and BMP4. Invasive NSCs expressed Podoplanin (PDPN) and p75NGFR (Ngfr) at the plasma membrane after expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 56 publications
3
13
0
1
Order By: Relevance
“…FGF-1 induced fibroblast invasion, but not migration, whereas PDGF-AB and thrombin induced fibroblast migration, but not invasion. Of the mediators we found to induce invasion of primary mouse lung fibroblasts, PDGF-BB, EGF, and FGF-1 have been previously noted to induce invasion of fibroblasts isolated from other sources (32,(36)(37)(38), and LPA, FGF-1, and FGF-2 have been previously noted to induce cancer cell invasion (38)(39)(40)(41). Consistent with our finding that these mediators are able to induce fibroblast invasion ex vivo, we found evidence to suggest that these mediators all contribute to the non-cell-autonomous fibroblast invasion induced in vivo in the bleomycin model: knockdown of lung fibroblast PDGFRb, LPA 1 , EGFR, or FGFR2 expression each, by themselves, significantly decreased fibroblast invasion induced by BAL from bleomycin-challenged mice.…”
Section: Discussionmentioning
confidence: 75%
“…FGF-1 induced fibroblast invasion, but not migration, whereas PDGF-AB and thrombin induced fibroblast migration, but not invasion. Of the mediators we found to induce invasion of primary mouse lung fibroblasts, PDGF-BB, EGF, and FGF-1 have been previously noted to induce invasion of fibroblasts isolated from other sources (32,(36)(37)(38), and LPA, FGF-1, and FGF-2 have been previously noted to induce cancer cell invasion (38)(39)(40)(41). Consistent with our finding that these mediators are able to induce fibroblast invasion ex vivo, we found evidence to suggest that these mediators all contribute to the non-cell-autonomous fibroblast invasion induced in vivo in the bleomycin model: knockdown of lung fibroblast PDGFRb, LPA 1 , EGFR, or FGFR2 expression each, by themselves, significantly decreased fibroblast invasion induced by BAL from bleomycin-challenged mice.…”
Section: Discussionmentioning
confidence: 75%
“…In gliomas, IGFBP2 is considered to be an oncogene that causes glioma progression through integrin/ILK/NF-kB pathway (Phillips et al, 2016). According to reports, Podoplanin (PDPN) was a novel candidate gene that might play an essential role in glioblastoma pathogenesis and response to treatment (Sailer et al, 2013;Krishnan et al, 2018). However, these genes and the related signaling pathways and mechanisms involved are still not clear enough.…”
Section: Discussionmentioning
confidence: 99%
“…Witty et al (2014) have reported the presence of podoplanin as a marker of epicardial lineage cells generated from human pluripotent stem cells by stage-specific activation of the BMP and Wnt signaling pathway. Sailer et al (2013) have studied the properties of rat neural stem cells, normally non-invasive. However, in the presence of FGF2 and BMP4 they acquire a migratory and invasive phenotype.…”
Section: In Vivo Studiesmentioning
confidence: 99%